SALIVARY BIOMARKERS IN ORAL LEUKOPLAKIA-A REVIEW - Dr.T.N.UMAMAHESWARI, (International Journal of Pharma and Bio Sciences, 2015)
Early diagnosis of oral cancer, which accounts for 3rd most common cancer in Indian population, is essential to improve the quality of life in such patients. Squamous Cell Carcinoma accounts for majority of oral cancer and leukoplakia is one of the most common potentially malignant lesions of the oral mucosa with malignant transformation rate ranging from 0.6 to 20%. There are many invasive & non-invasive diagnostic techniques to assess the malignant risk potential in cancer risk patients. One such non-invasive diagnostic technique to evaluate cancer risk potential in potentially malignant disorders such as leukoplakia is sialodiagnosis. Salivary biomarkers are used in diagnosis of oral & systemic diseases. This article aims in reviewing the various salivary biomarkers in oral leukoplakia to identify the most significant diagnostic & prognostic marker of oral carcinoma.